Law Enforcement Regarding Criminal Offenses Involving Online Gambling Committed by Minors - Akmal Syaefulloh; Ismayana Ismayana (International Journal Labs, 2026)
The increasing involvement of young people in illegal online gambling is facilitated by the rapid advancement of information technology. Children, who should be focusing on their education and personal development, are easily drawn into online gambling due to a lack of parental guidance, limited understanding of digital tools, and financial pressures that drive them to seek quick money. This research aims to determine how the law is enforced against child perpetrators of online gambling and to identify the factors that drive such behaviour. The study employs a qualitative approach with a focus on actual legal practices in the Cirebon area. Data were collected through interviews with the Cirebon City Police, document review, and analysis of primary and secondary legal sources. The findings indicate that a solid legal framework exists for handling child perpetrators of online gambling under the applicable laws, and that the police have endeavoured to comply with the procedures established by the Juvenile Criminal Justice System. However, challenges persist in law enforcement, including a lack of expertise in digital forensics, limited use of artificial intelligence technology for early detection, and insufficient digital literacy among the public. The factors driving children toward online gambling can be categorised into three main areas: financial pressures generating economic motives, the desire for instant rewards driven by psychological factors, and family dysfunction resulting from inadequate parental attention and supervision. The research concludes that an effective response requires a combined approach encompassing not only firm law enforcement action, but also preventive measures such as economic support for families and the improvement of digital literacy.